Self-Esteem Of Adolescents Who Failed To Be Admitted To Public Universities - Yeni Apriliany; Reni Nuryani; Sri Wulan Lindasari (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2023)
Adolescents with failure tend to make self-esteem feel dissatisfied with themselves and their sense of wanting to be someone else, more often experience negative emotions, difficult to accept failure and excessive disappointment when failing. The purpose of this study to see a picture of self-esteem of adolescents who failed to be admitted to public universities, this study uses a quantitative descriptive design with a population of adolescents who failed to be admitted to public universities. The sampling technique in this study using simple random sampling, with a sample of 119 respondents and the method of data collection is by distributing questionnaires survey. The research instrument used Rosenberg self esteem scale that has been modified by the researcher and tested for validity and reliability. Validatas test results showed 0.868 then for the reliability results have a Cronbach Alpha value of 0.760. The results showed 7.57% had self-esteem problems after failing in public college admissions and 92.43% had no self-esteem problems.